2019
DOI: 10.1101/627232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple non-auditory cortical regions innervate the auditory midbrain

Abstract: Our perceptual experience of sound depends on the integration of multiple sensory and cognitive domains, but the networks sub-serving this integration are unclear. There are connections linking different cortical domains, however we do not know if there are also connections between multiple cortical domains and subcortical structures. Retrograde tracing in rats revealed that the inferior colliculus -the auditory midbrain -receives dense descending projections from not only the auditory cortex, but also the vis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…These cells seemed to be enriched at the caudolateral side of the dorsal IC (Figure 8C–D). Four of the 41 cells were found in the Gad2;Ai96 line, in agreement with a recent report that inputs from motor or somatosensory cortex can directly target GABAergic cells (Olthof et al, 2019), and the remainder in the GP4.3 line, making them 1% of GABAergic and 4% of investigated glutamatergic cells, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These cells seemed to be enriched at the caudolateral side of the dorsal IC (Figure 8C–D). Four of the 41 cells were found in the Gad2;Ai96 line, in agreement with a recent report that inputs from motor or somatosensory cortex can directly target GABAergic cells (Olthof et al, 2019), and the remainder in the GP4.3 line, making them 1% of GABAergic and 4% of investigated glutamatergic cells, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Numerous studies have shown both ascending and descending somatosensory projections to the IC (Aitkin et al, 1981; Künzle, 1998; Jain and Shore, 2006; Zhou and Shore, 2006; Lesicko et al, 2016; Patel et al, 2017), as well as from nuclei that are upstream from IC such as the dorsal cochlear nucleus, which also receive somatosensory inputs (Wu et al, 2014). In addition, the IC receives inputs from the motor cortex (Cooper and Young, 1976; Olthof et al, 2019). This prompted us to investigate whether these ‘spontaneous’ activities could be attributed to non-auditory inputs.…”
Section: Resultsmentioning
confidence: 99%
“…Inputs from IC may convey nonauditory "multisensory" signals and could be one of the main sources of multisensory input to DCN to underlie functions such as cancellation of self-generated sounds. The IC is a major hub of multisensory integration, processing axonal inputs from somatosensory, visual and auditory cortices (Cooper and Young, 1976;Olthof et al, 2019), and somatosensory brainstem nuclei (Tokunaga et al, 1984;Paloff and Usunoff, 1992). The cell types in the granule cell region are known to process extrinsic nonauditory signals from regions of various modalities, and the relative balance among these contributions is unclear (Ryugo et al, 2003).…”
Section: Role Of Descending Multisensory Projections In Hearingmentioning
confidence: 99%